2018
DOI: 10.1111/bcp.13574
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of CYP3A4*20, UGT1A1*37 and UGT1A1*28 variants in irinotecan‐induced severe toxicity

Abstract: Severe irinotecan-induced toxicity is associated with UGT1A1 polymorphisms. However, some patients develop side-effects despite harbouring a normal UGT1A1 genotype. As CYP3A4 is also an irinotecan-metabolizing enzyme, our study aimed to elucidate the influence of the CYP3A4*20 loss-of-function allele in the toxicity profile of these patients. Three-hundred and eight metastatic colorectal cancer patients treated with an irinotecan-containing chemotherapy were studied. The presence of CYP3A4*20, UGT1A1*37 and UG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Our findings support these negative results as we found no associations with severe neutropenia in the 307 patients analyzed. These data, together with the significant association obtained with the UGT1A1*28 marker (P = 0.037) in a previous study by our group (Riera et al, 2018), lead us to infer that UGT1A1 is a more powerful predictor of severe neutropenia than ABCB1.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Our findings support these negative results as we found no associations with severe neutropenia in the 307 patients analyzed. These data, together with the significant association obtained with the UGT1A1*28 marker (P = 0.037) in a previous study by our group (Riera et al, 2018), lead us to infer that UGT1A1 is a more powerful predictor of severe neutropenia than ABCB1.…”
Section: Discussionsupporting
confidence: 70%
“…A total of 176 patients had been enrolled in clinical trials ( Marcuello et al., 2011 ; Páez et al., 2019 ). The presence of the UGT1A1*28 , UGT1A1*37 , and UGT1A1*36 alleles was determined in a previous study ( Riera et al., 2018 ). Table 1 shows patients’ clinical characteristics along with UGT1A1 genotype status.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CYP3A4 and CYP3A5 are responsible for the oxidation of irinotecan into the inactive metabolites APC, M4 and NPC. Some researchers have studied the possible association of polymorphisms on these genes and chemo-related toxicity but have not found any positive correlation [ 68 , 96 , 112 ], probably because over 80% of variants in CYP genes coding regions are very rare and the sample sizes of these studies were not large enough [ 113 ]. It has also been suggested that their enzymatic function might be altered by non-genetic factors such as diet, concomitant medications, altered liver function or patient’s performance status [ 114 ].…”
Section: Pharmacogenetics: Candidate Gene Studiesmentioning
confidence: 99%
“…Even though the risk of severe irinotecan-related toxicity can be significantly decreased if the initial dose in UGT1A1*28 homozygous patients is reduced, not all toxicity can be prevented with this strategy. Factors such as other UGT1A1 variants can also influence UGT1A1 enzyme activity [15]. In the Asian population, where the UGT1A1*28 allele frequency is less than 0.16, a more common variant, UGT1A1*6, can predict irinotecan-induced toxicities better than the UGT1A1*28 polymorphism [16].…”
mentioning
confidence: 99%